Mesenchymal Stem Cell-Derived Exosomes Induced by IL-1β Attenuate Urethral Stricture Through Let-7c/PAK1/NF-κB-Regulated Macrophage M2 Polarization - Chen YH; Dong RN; Hou J; Lin TT; Chen SH; Chen H; Zhu JM; Chen JY; Ke ZB; Lin F; Xue XY; Wei Y; et al. (Dove Medical Press, 2021)
Ye-Hui Chen,1,* Ru-Nan Dong,1,* Jian Hou,1,* Ting-Ting Lin,1,* Shao-Hao Chen,1 Hang Chen,1 Jun-Ming Zhu,1 Jia-Yin Chen,1 Zhi-Bin Ke,1 Fei Lin,1 Xue-Yi Xue,1 Yong Wei,1 Ning Xu1,2 1Department of Urology, Urology Research Institute, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People's Republic of China; 2Fujian Key Laboratory of Precision Medicine for Cancer, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People's Republic of China*These authors contributed equally to this workCorrespondence: Ning Xu; Yong WeiDepartment of Urology, Urology Research Institute, the First Affiliated Hospital, Fujian Medical University, 20 Chazhong Road, Fuzhou, 350005, People's Republic of ChinaTel +86-059187981687Email drxun@fjmu.edu.cn; weiyong2017@fjmu.edu.cnBackground: Urethral stricture is a clinical challenge for both patients and clinicians. Post-traumatic urethral stricture is associated with formation of scar tissue caused by excessive inflammation. The aim of this study is exploring potential therapeutic strategies for this condition.Methods: In vivo experiments on New Zealand rabbits and in vitro experiments on THP-1 monocytes and urethral fibroblasts were performed to investigate the effects on post-traumatic urethral stricture of exosomes isolated from IL-1β-treated mesenchymal stem cells (Exo-MSCsIL− 1β) and the role of macrophage M2 polarization in this process. Additionally, related signaling and mechanism behind were explored.Results: In a New Zealand rabbit model of post-traumatic urethral stricture, injection of Exo-MSCsIL− 1β significantly reduced urethral stricture and collagen fiber accumulation compared with Exo-MSCs. Addition of Exo-MSCsIL− 1β to THP-1 monocytes in vitro induced M2 macrophage polarization, which, in turn, inhibited activation of urethral fibroblasts and synthesis of collagen. Mechanistically, Exo-MSCsIL− 1β were found to contain high levels of the microRNA let-7c, and luciferase reporter assays showed that let-7c interacted with the 3'UTR of PAK1 mRNA. Transfection of THP-1 cells with a let-7c mimic downregulated PAK1 expression and inhibited activation of the NF-κB signaling pathway.Conclusion: These results support a role for let-7c-containing Exo-MSCsIL− 1β in reducing urethral stricture via inhibition of PAK1-NF-κB signaling, M2 macrophage polarization, and differentiation of urethral myofibroblasts.Keywords: urethral stricture, mesenchymal stem cells, polarization of macrophages, exosomes, let-7c